An enhanced electrochemical platform based on graphene oxide and multi-walled carbon nanotubes nanocomposite for sensitive determination of Sunset Yellow and Tartrazine. (1st January 2016) - Qiu, Xinlan; Lu, Limin; Leng, Jing; Yu, Yongfang; Wang, Wenmin; Jiang, Min; Bai, Ling
Highlights: Stable dispersion of GO/MWCNTs composite was produced by sonication mixing. GO/MWCNTs electrode showed high electrochemical activity for Yellow and Tartrazine. It can be used for the determination of Yellow and Tartrazine. The developed method can detect Yellow and Tartrazine in practical sample. Abstract: A novel electrochemical platform was designed for the simultaneous determination of Sunset Yellow (SY) and Tartrazine (TT), synthetic food dyes, by combining the signal amplification properties of graphene oxide (GO) and the excellent electronic and antifouling properties of multi-walled carbon nanotubes (MWCNTs). Stable dispersion of GO/MWCNTs composite was produced by sonication mixing. Compared with glassy carbon, MWCNTs and GO electrodes, GO/MWCNTs electrode exhibited strong enhancement effect and greatly increased the oxidation signal of SY and TT. Under optimized conditions, the enhanced anodic peak currents represented the excellent analytical performance of simultaneous detection of SY and TT in the range of 0.09–8.0 μM, with a low limit of detection of 0.025 μM for SY and 0.01 μM for TT ( S / N = 3), respectively. To further validate its possible application, the proposed method was successfully used for the determination of SY and TT in orange juice with satisfactory results.